L2MSS in the Saudi Arabian context: item, scale, and external validity analysis - Almesaar, Oun (Frontiers in Education, 2024)
With English being the modern lingua franca, educational policies in Saudi Arabia were recently changed in order to provide better English language education to Saudi students. In spite of the government's efforts to improve English proficiency, most Saudi students do not benefit sufficiently from the new curricula. Language 2 Learning Motivation Self-System (L2MSS), proposed by Dörnyei, provides a potential framework for understanding determinants of English proficiency among Saudi students. The pilot study first addressed the internal reliability, factor structure and item-level performance (classical model and IRT) of two new questionnaires developed to complement L2MSS with measures of cognitive, emotional, and behavioural aspects of attitude towards English. The main study focused on relationship between L2MSS and related variables with performance on an English test based on TOEIC. The study has shown that, while Saudi students tend to be motivated to learn English, L2MSS scores are not related to performance on an objective test of English proficiency. Moreover, the two new questionnaires, while associated with L2MSS, are not associated with English test performance. Exploratory factor analysis (with maximum likelihood extraction and direct oblimin rotation) of all L2MSS items resulted in a general L2MSS factor (29% variance), factors 2 (7% variance) and 3 (3%) had mixed loadings of "ought-to self" and L2 experience items, while factor 4 (2.7%) mainly had unique ideal self-loadings.